2005
DOI: 10.1902/jop.2005.76.8.1227
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Local Adjuncts to Scaling and Root Planing in Periodontal Disease Therapy: A Systematic Review

Abstract: Whether such improvements, even if statistically significant, are clinically meaningful remains a question. A substantial agenda of future research to address this and other issues (e.g., costs, patient-oriented outcomes) is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
171
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(193 citation statements)
references
References 46 publications
15
171
0
7
Order By: Relevance
“…Another systematic review corroborated our findings and showed that the most positive results occurred for exactly these substances and that their local administration generally reduced PD levels significantly [73]. However, when compared to SRP alone, the benefit in this study seemed to be rather small (0.1-0.5 mm).…”
Section: Discussionsupporting
confidence: 86%
“…Another systematic review corroborated our findings and showed that the most positive results occurred for exactly these substances and that their local administration generally reduced PD levels significantly [73]. However, when compared to SRP alone, the benefit in this study seemed to be rather small (0.1-0.5 mm).…”
Section: Discussionsupporting
confidence: 86%
“…However, key questions facing periodontitis and general dentists is whether SRP accompanied by use of an adjunctive antimicrobial agent improves patient outcome over time more than SRP alone in chronic periodontitis cases [2]. Mechanical debridement alone may fail to remove pathogenic organisms because of their location in sub epithelial connective tissue and crevicular epithelial cells [3][4][5][6][7][8].…”
Section: Inrtoductionmentioning
confidence: 99%
“…In a systematic review conducted by Bonito Arthur J et al, [2], it was found that among the locally administered adjunctive antimicrobials the most positive results occurred from tetracycline, minocycline, metronidazole and chlorhexidine. Hyaluronic Acid (HA) is a recent addition to the local chemotherapeutic agents.…”
Section: Inrtoductionmentioning
confidence: 99%
“…Overall efficacy of local antibiotic therapies has been evaluated using meta-analysis of fifty articles, each reporting studies of at least six months follow-up (Bonito, et al, 2005). The meta-analysis considered studies of the addition of local adjuncts and found such additions provide generally favorable but minimal differences.…”
Section: Antimicrobialmentioning
confidence: 99%